Flipped classroom resources to help students prepare for animal handling and clinical skills practicals. Issue 9 (19th June 2021) - Mitchard, Louisa; Catterall, Alison; Brown, Sam; Gray, Lucy; Squire, Lucy; O'Shaughnessy, Sarah; Baillie, Sarah
Abstract: This article describes our experiences developing flipped classroom resources to help veterinary nursing and veterinary students prepare for animal handling and clinical skills practicals. The process involved planning, deciding what to include in the flipped component, providing training for the team, adopting a standardised template for the design and developing resources for the learning activities. A series of flipped classrooms has been developed for use by our students and these are being added to our open-access website for the wider community.